DAGESTAN PEOPLE - HEROES OF THE SOVIET UNION - Davudov, O M (History, Archeology and Ethnography of the Caucasus, 2015)
During the years of severe trials of the Great Patriotic War, Dagestan, together with the peoples of the USSR, actively participated in the struggle against the fascist aggressors. On the territory of the Land of Mountains, 44 and 58 armies were formed, consisting of thousands of Dagestanis, 91 rifle divisions, the Makhachkala rifle division of the NKVD, the 714th anti-aircraft artillery regiment, consisting of 980 Dagestan girls, the Buynaksk infantry school, a separate Dagestan squadron unit, a separate Dagestan squadron unit. Kizlyar cavalry squadron, crew of the armored train "Komsomolets Dagestan." Detachments of the national militia were created in the republic, in which at the beginning of October 1941 there were about 12 thousand people. To combat the enemy landings, scouts and spies, by the end of 1941, 39 fighter units were created in the republic, in which there were more than 2 thousand people. From Dagestan, over 142 thousand Dagestan fought on the fronts of the Great Patriotic War. This number did not include about 16 thousand people called up from Kizlyar, Tarumovsky, Nogai districts and the city of Kizlyar. Fighting on the fronts of the Great Patriotic War, Dagestanis showed courage and heroism. Tens of thousands of Dagestan front-line soldiers gave their lives for their Motherland. Many of them were awarded military orders and medals, 73 Dagestanis were awarded the title Hero of the Soviet Union, 7 people became full holders of the Order of Glory. We give below information about them. They are compiled by OM. Davudov. At the same time, materials from the Heroes of the Soviet Union sites are used.